International Journal of Primatology The Official Journal of the International Primatological Society - Setchell, Joanna M.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
The International Journal of Primatology is a multidisciplinary forum devoted to the dissemination of current research in fundamental primatology. Publishing peer-reviewed, high-quality original articles which feature primates, the journal gathers laboratory and field studies from such diverse disciplines as anthropology, anatomy, ecology, ethology, paleontology, psychology, sociology, and zoology. Original Research Articles address various aspects of primatology and the conservation of primates and their habitats. Articles reporting on endangered or threatened species are highlighted, to raise awareness of the plight of primates. In addition to original research papers, the International Journal of Primatology considers data papers, review articles, book reviews, and News & Views pieces. News & Views are short communications or critical commentaries on recently published papers in the International Journal of Primatology or other journals. These are limited to 1000 words and 5 references, with a maximum of one figure or table and no abstract. The International Journal of Primatology welcomes proposals for guest-edited Special Issues or Special Sections on a particular theme. A Special Issue is one whole issue of the journal and should include approximately 12-14 articles. A Special Section is a smaller collection of articles. Articles in a Special Issue or Section can include original research articles, reviews, commentaries and guest editorials. To propose a Special Issue, please send the following information to the Editor-in-Chief, Dr Joanna (Jo) M Setchell (joanna.setchell@durham.ac.uk): A proposed title Proposed Guest Editors A 250 word abstract that explains why the topic is important A list of the intended contributions An estimated timeline for submissions.
Keywords: Human genetics; Animal ecology; Evolutionary biology; Zoology; Anthropology; Evolutionary Biology; Zoology; Animal Genetics and Genomics; Anthropology; Animal Ecology; Human Genetics